The Role of Community Centers in Promoting the Sport Practicing in Saudi Society – The Descriptive Study on Community Centers in Jeddah – - Alghamdi, Samah Mohammed Alhmood (Journal of Humanities & Social Sciences, 2021)
This study aims to reveal the role of the community centres in promoting sports activities the in Saudi society, and to identify the motives that enhance practicing sports in the Saudi society, and to identify the obstacles that limit practicing sports in the Saudi society, and in order to reach these goals the study relied on the descriptive approach and on the questionnaire tool for collecting data, and the sample members were beneficiaries of sporting activities in community centres in Jeddah. The study concluded that community centres have increased practicing sports among Saudi society, and that individuals who benefit from sports activities in community centres are mostly the age group between 19-30 years old, the study has also found that practicing sports activities decreases when the age variable increases. Entertainment motivations for practicing sports have obtained the highest rating among beneficiaries of sports activities in community centres, where it has scored more than health, psychological, and social motives, the study has also found that social motivations enhance sports practice in Saudi society, especially the tendency of those who actually practice sports in the community centres to play sports with other people. And finally; the study points to the bearing that a percentage of the sample members find "societal obstacles" limiting the physical exercise of Saudi society to some degree.
Keywords: sports sociology; neighborhood centers; sports practice; health community awareness; Saudi society